Code-Switching in Digital Communication: A Study of Bilingual Language Use in Popular Platforms - Wulandari, Citra Eka; Hadianti, Asti Nur; Fhadilathusy, Siti Mutiara (International Journal of Language and Culture, 2025)
Code-switching is increasingly prevalent in digital communication, particularly on popular platforms such as Instagram, WhatsApp, TikTok, and Twitter. This trend reflects a shift in communication practices within increasingly multilingual and global digital spaces. This study examines code-switching in digital communication and the factors influencing this phenomenon, including social context, audience, and the types of platforms used. This research analyses various journals, articles, and previous studies on code-switching in digital contexts using a qualitative approach and a literature review method. The results show that code-switching is influenced by social and psychological factors, with speakers often switching languages to adapt to their audience or to express cultural identity. Other findings indicate that code-switching is a communication strategy that enriches digital interaction and strengthens user social ties. Additionally, local languages are more dominant on private platforms, while English is more frequently used on platforms with international audiences. This research provides new insights into the dynamics of language in digital communication and its relevance to shaping social identity in cyberspace.